Evaluation of the combined use of papanicolaou screen test and the polymerase chain reaction for the identification of patients at risk of cervical cancer - Moysés, Natalia; Balthazar, Daniela S.; Afonso, Larissa A.; Oliveira, Ledy H.S.; Cavalcanti, Silvia Maria B. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: in the last few years, the interest on Human Papillomavirus (HPV) has emerged due to the evidence of their carcinogenic potential, especially on the female genital tract. In the last fifty years, the screening diagnosis has been carried out by Papanicolaou test (Pap). Nevertheless, literature describes a high rate of false-negative and false-positive samples. Objective: since an early detection is crucial to diminish the risk of cervical cancer, we aimed to analyze the use of HPV DNA detection by PCR as complementary test to routine screening. Methods: nearly 450 female smears were obtained from the DNA Bank of the Virological Diagnosis Laboratory from UFF. HPV prevalence was evaluated by using MY09/11 consensus primers and was compared to Pap test. Results: our results showed that 67.5% of the studied samples were normal tissues, among them 85.6% were negative by PCR but 14.4% were HPV infected. The remaining 32.8% were altered by Pap test. Among them, HPV DNA detection by PCR revealed a prevalence of 56.7% in ASCUS, 87.5% in LSIL and 66,6% in carcinoma. Kappa index showed a good agreement between tests (0.80). The Positive Predictive Value was considered low (58%) pointing out that important cases may be misdiagnosed as false-negatives. On the other hand, the Negative Predictive Value was considered high (90,5%) indicating that PCR should not be used as a screening test, but as a complementary one, revealing true negatives when associated to a normal result in Pap test. HPV positive samples detected by MY PCR were typed and the prevalence obtained for the different types was: 48% HPV 16,17% HPV 33, 13% HPV 18,18% HPV 6 and 19% were undetermined because of non tested primers or technical problems. Conclusion: analyzing the results we concluded the combination of both tests is the best diagnostic procedure, allowing a more efficient evaluation of cancer risk and thus helping in prevention programs.